Perancangan Tata Letak Gudang Finish Good pada Perusahaan Komponen Otomotif - Febriza Imansuri; Rahmat Dwi Febriyanto; Fredy Sumasto; Emi Rusmiati; Indra Rizki Pratama; Feby Gusti Dendra (Jurnal Serambi Engineering, 2024)
PT HMG is a manufacturing company that uses injection moulding machines to produce plastic components for the electronics, automotive and engineering industries. The problems found at PT HMG are that the finished goods are not placed in an orderly manner or that the goods are not neatly arranged. The placement of these goods is still mixed with goods that have run out, so the process of moving goods is not optimal and the risk of picking inappropriate goods is higher. This has an impact on delivery errors and the sub-optimal process of moving goods can cause delays in delivery to the customer. Dedicated storage is a layout design method for storing goods where the storage location is fixed. This method uses throughput as areference when positioning goods so that goods with a high flow of movement are prioritised to minimise the time it takes to move goods to I/O points. The difference in the total distance to the I/O point for the proposed layout is 17,809 metres, or 9% of the previous layout. With this layout improvement, the company is able to reduce the waste caused by material handling activities in the finished goods warehouse.